Study of the Role of Customary Institutions in Government Systems in Hitu Lama State, Leihitu District, Central Maluku Regency - Latuconsina, Nurainy; Fretes, Judy De; Tehuayo, Johan (Pusat Penelitian dan Pengabdian pada Masyarakat Sekolah Tinggi Ilmu Administrasi (STIA) Mataram, 2020)
Pemerintahan Negeri is a term used by people in Central Maluku regency in Maluku Province to state the system in the division of administrative territory at the village level. The term Negeri replaces the status of the village or kelurahan used in the regency. Pemerintahan Negeri has a spirit called Budaya Negeri (culture of Negeri). The spirit of Budaya Negeri in is a genelogical-territorial system in customary law unit immersed and used from the royal government system until now containing the characteristic and beliefs of local customs. In this system, the leader of the village or Negeri who runs the government is called Bapak Raja (The King). The position of Bapak Raja as the leader of the village-governmental system has been running for a long time. The culture of Pemerintahan Negeri is still believed to be the model of the customary government system in Central Maluku. This study aims to determine the role of costumary institutions in the Pemerintahan Negeri system in Hitu Lama, Central Maluku Regency. This study uses descriptive qualitative method. Data collection techniques used are direct observations, interviews, and documents analysis. The collected data are then analysed using reduction analysis techniques, data display (data presentation) and verification (drawing conclusions). The primary data sources in this study are taken from Bapak Raja of Hitu Lama, the costumary institution of Hitu Lama named